If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying k + -6 = -12 Reorder the terms: -6 + k = -12 Solving -6 + k = -12 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + k = -12 + 6 Combine like terms: -6 + 6 = 0 0 + k = -12 + 6 k = -12 + 6 Combine like terms: -12 + 6 = -6 k = -6 Simplifying k = -6
| 14s=98 | | 8(4x-6)=4(8x+7) | | 8x=12y-18 | | 5(x-7)+5=90 | | v-39=16 | | x(20)+(48-x)(40)=(35)(48) | | 8g=112 | | =x(20)+(48-x)(40) | | 3+10x-2=7x+37-3x | | 1/3(x-6)=1 | | -8(1-6x)-4=-x-12 | | 25-13=4(x-9) | | n-56=82 | | 5x-8-7=0 | | -1*22=-22 | | 6-8x=7x-9x+12 | | =x(20)+1 | | 9x+12x=168 | | 5y-7y=-8-12 | | -53-2[7-6(5+11)]-(2-3)-4= | | 12[2-x]=6 | | -9.5x=57 | | 2x^4-104x^2+294=0 | | 9x=-66 | | v+4=0 | | 2.5m=11 | | 3x-4+5x+6= | | b-10=-3 | | 22=18-25x | | -2(2b+2)+(5b-1)=0 | | y=-1/2(3)+2 | | 1.4q-4.2-1.6q=-1.2q-2.7 |